2006
DOI: 10.1073/pnas.0602280103
|View full text |Cite
|
Sign up to set email alerts
|

Long-term self-renewal and directed differentiation of human embryonic stem cells in chemically defined conditions

Abstract: Chemically defined medium (CDM) conditions for controlling human embryonic stem cell (hESC) fate will not only facilitate the practical application of hESCs in research and therapy but also provide an excellent system for studying the molecular mechanisms underlying self-renewal and differentiation, without the multiple unknown and variable factors associated with feeder cells and serum. Here we report a simple CDM that supports efficient self-renewal of hESCs grown on a Matrigel-coated surface over multiple p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
285
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 418 publications
(300 citation statements)
references
References 29 publications
7
285
2
1
Order By: Relevance
“…However, it is not clear whether the ESCs followed normal developmental sequences in these studies due to a lack of initial specification using developmentally relevant factors known to regulate pancreatic endoderm development. It has recently been shown that treatment of feeder-free hESC colonies with activin directs the differentiation of hESCs into PDX1 + pancreatic endoderm, although the developmental competence of the PDX1 + endoderm was not characterised in this study [8]. In our study, hESC-derived PDX1 + clusters were further differentiated into cells that produce insulin, proinsulin, C-peptide and glucagon upon transplantation.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…However, it is not clear whether the ESCs followed normal developmental sequences in these studies due to a lack of initial specification using developmentally relevant factors known to regulate pancreatic endoderm development. It has recently been shown that treatment of feeder-free hESC colonies with activin directs the differentiation of hESCs into PDX1 + pancreatic endoderm, although the developmental competence of the PDX1 + endoderm was not characterised in this study [8]. In our study, hESC-derived PDX1 + clusters were further differentiated into cells that produce insulin, proinsulin, C-peptide and glucagon upon transplantation.…”
Section: Discussionmentioning
confidence: 49%
“…To date, only a few studies have suggested the potential of hESCs to differentiate into insulin-producing cells [5][6][7][8]. It was previously reported that insulin-producing cells were found in EBs after spontaneous in vitro differentiation of hESCs [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These cells initially were cultivated on a layer of feeder cells in a serum‐ or KSR‐supplemented medium,104 but in anticipation of clinical applications, the efforts shifted to the development of culture conditions that are feeder‐free and xeno‐free (Table 5). 105, 106, 107, 108, 109, 110, 111 Among these, the E8 medium that was developed by Guokai Chen et al. has become popular.…”
Section: History Of Cell Culture Mediamentioning
confidence: 99%